1982
DOI: 10.1073/pnas.79.19.6084
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and purification to homogeneity of a rat brain protein (GABA-modulin).

Abstract: y-Aminobutyric acid (GABA)-modulin is a brain neuropeptide that appears to modulate specific high-affinity (20 nM) GABA recognition sites in brain. When added to crude synaptic membranes this peptide inhibits binding of [3H]GABA to the high-affinity site and prevents facilitation of [H]diazepam binding elicited by GABA. GABA-modulin has been purified to homogeneity by ammonium sulfate precipitation, gel chromatography, and reverse-phase HPLC. Homogeneity was confirmed by a variety of means, including chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…This treatment precipitates approximately 80% of the proteins, leaving the DBI in solution in the 48,000 x g supernatant. Among the proteins precipitated by the ammonium sulfate treatment is GABA-modulin (30). Removal of GABA-modulin at this stage facilitates the purification of DBI because GABA-modulin is eluted in the HPLC reversed-phase procedure (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment precipitates approximately 80% of the proteins, leaving the DBI in solution in the 48,000 x g supernatant. Among the proteins precipitated by the ammonium sulfate treatment is GABA-modulin (30). Removal of GABA-modulin at this stage facilitates the purification of DBI because GABA-modulin is eluted in the HPLC reversed-phase procedure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of GABA-modulin at this stage facilitates the purification of DBI because GABA-modulin is eluted in the HPLC reversed-phase procedure (Fig. 1) very close to DBI and because GABA-modulin also may inhibit [3H]diazepam binding by virtue of its role on the modulation of GABA recognition sites (30).…”
Section: Discussionmentioning
confidence: 99%
“…The increased binding may result from better removal of endogenous GABA, removal of some other inhibitor of GABAA receptor binding such as GABA-modulin (18) or stabilization of a high-affinity conf ormation of the receptor protein. Drug competition study for muscimol binding revealed the presence of specific GABAA receptors in human brain, and potentiating effect of diazepam on muscimol bindings further suggested that they represent the functional GABA/benzodiazepine receptor complex (19).…”
Section: Discussionmentioning
confidence: 99%
“…rapidly doubles the number of high-affinity binding sites for [3H]muscimol and at the same time shifts the slope of the Hill plot from 1 to 1.66, denoting positive cooperativity at the receptor level. Perhaps diazepam produces an allosteric change of GABA recognition sites by altering the inhibitory constraint imposed on GABA receptors by GABA-modulin (3,4,23), which we believe functions as an inhibitory coupler between the GABA recognition sites and the Cl-channels (24 (1984) produce maximal pharmacological effects. Indeed, as shown in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In this respect, [3H]muscimol appears to be an almost ideal ligand for ex vivo experiments because its metabolism occurs preferentially at the periphery and by the mechanism of transamination (13,21). The transaminated metabolites are unlikely to enter the brain, and even if they enter, because of the loss of the amino group (13,21) The presence of a diazepam-sensitive mechanism that allosterically controls the number of high-affinity binding sites for GABA, which was suggested by in vitro experiments (3,(7)(8)(9)23), is confirmed by these ex vivo measurements of GABA binding sites. Diazepam (1.5-3 ,umol/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%